2016
DOI: 10.5714/cl.2016.20.081
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of CH4and CO2adsorption by fluorinated graphene

Abstract: Phenomena related to global warming have been of particular interest among researchers, strongly encouraging them to identify various methods of adsorbing contributing gases, such as CH 4 and CO 2 [1,2]. Many adsorbents have been widely proposed and studied to remove greenhouse gases from the atmosphere and protect the environment [3,4]. Carbon-based materials for adsorption are an intriguing subject owing to their very high specific surface area, low weight, and elasticity [5,6]. Among various carbonaceous ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…The adsorption energies of the three organic molecules are smaller than 0.5 eV, further verifying that the adsorption of the three organic molecules is a kind of typical physisorption. In fact, for these organic molecules, the adsorption type on borophene is the same as that on graphene. For example, the adsorption energy of CH 4 on graphene is about −0.15 eV, very close to the result of borophene obtained here (−0.17 eV). On the two 2D nanomaterials CH 4 adopts the same adsorption type.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The adsorption energies of the three organic molecules are smaller than 0.5 eV, further verifying that the adsorption of the three organic molecules is a kind of typical physisorption. In fact, for these organic molecules, the adsorption type on borophene is the same as that on graphene. For example, the adsorption energy of CH 4 on graphene is about −0.15 eV, very close to the result of borophene obtained here (−0.17 eV). On the two 2D nanomaterials CH 4 adopts the same adsorption type.…”
Section: Resultssupporting
confidence: 77%
“…In fact, for these organic molecules, the adsorption type on borophene is the same as that on graphene. 47−49 For example, the adsorption energy of CH 4 on graphene is about −0.15 eV, 47 very close to the result of borophene obtained here (−0.17 eV). On the two 2D nanomaterials CH 4 adopts the same adsorption type.…”
Section: Resultssupporting
confidence: 76%
“…Geometries were optimized, and the total energies and forces were calculated using a planewave basis set with the projector augmented wave (PAW) method [ 36 ]. The generalized gradient approximation (GGA) with the Perdew–Burke–Ernzerhof (PBE) exchange-correlation functional [ 37 ] was used, and the planewave cutoff energy was set to 500 eV; the GGA-PBE functional has been successfully used to describe carbon-based systems [ 38 , 39 , 40 , 41 , 42 , 43 ]. All structures were optimized such that the total energy converged to less than 1.0 × 10 −6 eV per atom and the maximum force converged to below 0.05 eV Å −1 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…DFT+ U calculations were implemented within the Vienna Ab Initio Simulation Package (VASP). , We used Grimme’s dispersion corrections for describing van der Waals interactions in all calculations, and the Coulomb interaction parameter U was set to 4.0 eV for Fe. , The generalized gradient approximation (GGA) of the Perdew–Burke–Ernzerhof (PBE) functional was used to calculate exchange-correlation energies; the GGA-PBE functional has been shown to described carbon-based systems reasonably well. The configuration of GQD prefers to be the hexagonal graphene network along with the zigzag orientation . In addition, Hassanien et al showed that C 96 H 24 has a lower HOMO–LUMO gap than the gap of other possible sizes of GQD.…”
Section: Computational Detailsmentioning
confidence: 99%